How to Unread Shelley Jackson ? - Stéphane Vanderhaeghe (Transatlantica)
This article aims at examining the activity of reading as it is precisely questioned by Shelley Jackson’s novel, Half Life. Playing on binary oppositions and twinning, the text undoes itself as it displays its attraction to blankness and erasure.